My Oxford reading tree dictionary - Hunt, Roderick; Brychta, Alex (Oxford : Oxford University Press, 2019)
Features all the favourite ORT characters from Floppy to Wilma Alphabet down the side of each page. 300 colour headwords and colour illustrations. Special topic words at the back to help with extended word level work. Introduction on how to get the best out of the dictionary
Primary
Keywords: English language -- Dictionaries; Picture dictionaries, English -- Juvenile literature; Encyclopedias and dictionaries